PENGATURAN TINDAK PIDANA DALAM UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (Tinjauan Fiqh Al- Bi’ah) - Ridwansyah, Muhammad (Jurnal Hukum dan Peradilan, 2017)
The setting of environmental law in Indonesia has started to improve since the Law Number 32 of 2009 on Environmental Protection and Management contains criminal act for every person who violates the provisions. It is stated in Article 98, 99, 100. This research method is a library or literature research which is conducted to gather secondary data in the field of environmental law and fiqh al-bi’ah. This research is normative law research while the nature of this research is descriptive analysis. It aimed to give a systematic illustration on legal norms that was found in law number 32 of 2009 and environmental fiqh accurately and the criminal sanctions review used in both arrangements. In this study there were two questions first, how is the arrangement of criminal act in Law No. 32 of 2009 on Environmental Protection Management. The second is whether the concept of fiqh al bi’ah is in line with Law No. 32 of 2009 on Environmental Protection Management. The result from this study is that the criminal act contained in the Law No. 32 of 2009 on Environmental Protection Management has not been enough to trap the environmental destroyer so that the government is expected to revise the unsuitable articles. Furthermore, the result of this research shows the similarity concept between fiqh al bi’ah and environmental governance in Indonesia. The concept offered by fiqh al bi’ah is a part of maqashidul syari’ah where Islam strongly recommended to maintain the environment. Keywords: environment, Fiqh Al-Bi’ah, Maqashidul Syari’ah